2010
DOI: 10.2174/138920110790909669
|View full text |Cite
|
Sign up to set email alerts
|

Small Heat Shock Proteins and Protein-Misfolding Diseases

Abstract: Small heat shock proteins (sHsps) are molecular chaperones ubiquitously distributed in numerous species, from bacteria to humans. A conserved C-terminal "alpha-crystallin" domain organized in a beta-sheet sandwich and oligomeric structure are common features of sHsps. sHsps protect cells against many kinds of stresses including heat shock, oxidative and osmotic stress. sHsps recognize unfolded proteins, prevent their irreversible aggregation and facilitate refolding of bound substrates in cooperation with ATP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 102 publications
0
46
0
Order By: Relevance
“…Furthermore, Bc inhibits the aggregation of glial acidic fibrillary protein (GAFP) and -syn which are associated with Alexander and Parkinson's disease (PD) pathologies, respectively [167,168]. Hsp20 and Hsp22 are also present at increased levels following neuronal stress associated with AD, PD, and ALS [169][170][171][172][173]. Hsp27 is also upregulated in AD and Neuman-Pick diseases [70].…”
Section: The Role Of Shsps In Neurodegenerative Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Bc inhibits the aggregation of glial acidic fibrillary protein (GAFP) and -syn which are associated with Alexander and Parkinson's disease (PD) pathologies, respectively [167,168]. Hsp20 and Hsp22 are also present at increased levels following neuronal stress associated with AD, PD, and ALS [169][170][171][172][173]. Hsp27 is also upregulated in AD and Neuman-Pick diseases [70].…”
Section: The Role Of Shsps In Neurodegenerative Diseasementioning
confidence: 99%
“…We have previously demonstrated that Bc prevents the aggregation of -syn, the principal protein in Lewy body deposits, and that Bc also binds to intact -syn fibrils 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 to prevent their further growth [106,107,167]. Furthermore, several sHsps (Hsp20, Hsp22, HspB7 and HspB9) inhibit the aggregation of the polyQ huntingtin protein responsible for Huntington disease and also protect against cell death triggered by the deposition of the aberrant protein [173,196]. Our subsequent studies have shown, however, that polyQ aggregation occurs in stages, and while Bc potently inhibits the first stage of fibril formation by the polyQ protein, ataxin (responsible for spinocerebellar ataxia), through interaction with its Josephin domain, the second stage of polyQ aggregation can still proceed [197].…”
Section: The Role Of Shsps In Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock protein (HSP) B1 (HspB1), previously known as Hsp27, is one of 11 members of the mammalian small HSP (sHSP) family (13,22). All members of this class have a molecular weight of 15,000 -40,000 and share a structural domain in their COOH-terminal halves, named the ␣-crystallin domain, that spans two putative actin-binding domains (36).…”
mentioning
confidence: 99%
“…All members of this class have a molecular weight of 15,000 -40,000 and share a structural domain in their COOH-terminal halves, named the ␣-crystallin domain, that spans two putative actin-binding domains (36). Furthermore, these proteins have demonstrated ATP-independent chaperone activity (14,22).…”
mentioning
confidence: 99%